Impact of castor meal on root-knot and free-living nematodes - Cecilia Helena Silvino Prata Ritzinger; Paul De Ley; Antoon Teunis Ploeg; Robert McSorley; Irma Tandingan De Ley (Scientia Agricola, 2014)
Soil amendment may enhance soil quality as well as reduce plant-parasitic nematode. Despite the many applications already undertaken using castor meal, its efficiency in controlling root-knot nematodes (RKN, Meloidogyne incognita) when applied to melon (Cucumis melo) is still not clear. Three different amounts of castor meal (Ricinus communis) applied were evaluated in microplots planted with melon either with or without RKN. The impact of castor meal on soil free-living nematode communities was also determined. Total nematode genera richness was estimated as 37 for the entire set of microplots sampled across both sampling dates. Rarefaction analysis resulted in 12 collector's curves out of the total of 30 that reached the horizontal asymptote. Univariate ANOVA with two factors yielded differences (p < 0.05) only with regard to the time factor. Simpson, Shannon, Evenness and Equitability indices showed a trend toward moderate increases by the end of the experiment, while the other indices were higher for tomato in pre-transplant sampling compared to harvest. Nematode community and diversity changed during the course of the experiment, although there was substantial confounding heterogeneity within and between the factorial combinations from the beginning. Root knot population was not reduced by the castor meal but increased throughout the period, regardless of treatment. RKN reduced melon yield, number and weight of melon.